5-Fluoro derivatives of 4-epi-isofagomine as d-galactosidase inhibitors and potential pharmacological chaperones for GM1-gangliosidosis as well as Fabry's disease. (February 2016) - Thonhofer, Martin; Gonzalez Santana, Andres; Fischer, Roland; Torvisco Gomez, Ana; Saf, Robert; Schalli, Michael; Stütz, Arnold E.; Withers, Stephen G.
Highlights: The first synthesis of 5-fluoro-isoimino sugars. The tertiary fluorine substituent is located at the branching point. Compounds exhibit improved α-galactosidase inhibition. Graphical abstract: Abstract: Electrophilic fluorination of an exocyclic methoxymethylene enol ether derived from N-tert-butyloxycarbonyl-1, 5-dideoxy-1, 5-imino-3, 4-O-isopropylidene-d - erythro -pent-2-ulose (11 ) provided the 5-fluoro derivative of the powerful β-galactosidase inhibitor 4- epi -isofagomine (8 ). This structural alteration, in combination with N-alkylation, led to considerably improved α-galactosidase selectivity. New compounds may serve as leads en route to new pharmacological chaperones for Fabry's disease.